Mecanismos de participación ciudadana desarrollados en las juntas de acción comunal del municipio de Soacha, Cundinamarca 2003 - 2012 (2013)
This document presents the progress and community building through the work done by the Community Action Boards of Soacha Cundinamarca, which through its development and management of programs and projects consistent with the identification of the particular needs of the population have been facilitating citizen participation in order to find alternative solutions to the complex problems affecting the neighbourhood community and take measures to enrich their community identity and its relations with the state.